APPLICATION OF SYNERGETIC METHODS AND THEORY OF ACCIDENTS - A. I. Borodin; N. N. Shash; N. N. Novikova (Стратегические решения и риск-менеджмент)
The condition of a global ecosystem comes nearer to the critical level that is reflected in social and economic development of society. At the present stage the analysis of the world for which the non-stationary behavior, social and economic and ecological crises connected with nonlinearity and multidimensionality of social and economic systems is characteristic has to become a subject of studying of economy and finance. A complex of models of accidents of global social and economic development is created. For carrying out the analysis the methodology of synergetic which is based on the theory of self-organization and a coevolution of difficult systems is chosen. The tools of modeling of the instability of socio-economic systems development which is conceptual and methodological basis, the catastrophe theory are considered. The algorithm is offered and the complex of models allowing to investigate type and nature of dynamics of development of the main macroeconomic indicators, to define possibility of formation of crises is constructed.